Capturing Teacher Readiness for Adapting Playful Virtual Reality in The Learning Process - Fatma Sukmawati; Jovita Ridhani; Sari Trisnaningsih (Teknodika, 2025)
Technological Content Knowledge (TCK) is a concept that describes the three main components of knowledge that a teacher must possess such as content, pedagogy, and technology. TCK is a concept of how technology and content affect each other. Teachers need to use technology and explain lesson concepts in the form of learning content with the help of certain technologies. However, the problem is that some teachers are not proficient in creating learning content using technology, even though they are already proficient in using technology in everyday life. So it is necessary to map the teacher's ability to use technology and create content so that training activities can be planned to complement their teaching needs. In response to these problems, we conducted mixed method research (qualitative and quantitative method) that aims to capture the level of technology and content-creating skills of teachers in Indonesia. We involved 20 Motivating Teachers from several elementary schools in Surakarta. This study is preliminary research as part of our ongoing Virtual Reality development project. Data were collected from questionnaires and documentation. Based on data analysis, 80.75% of teachers can use ICT, 79.67% teachers can apply ICT in learning, and only 30% can manage content. The next stage of this research will train these teachers to create subject matter content using playful technology, creating content about care for animals using virtual reality technology. This study provides recommendations to teachers and local governments that efforts to improve the quality of classroom learning can be started by improving teacher literacy technology first and then training them to create interesting technology-assisted learning content for students